Potential of The Biological Agent Bacillus sp. in Inhibiting Moler Disease and its Effects on The Growth and Production of Shallot (Allium ascalonicum L.) - F. Tsara Nafisah Yuwono; Yenny Wuryandari; Tri Mujoko (Universitas Labuhanbatu, 2025)
Shallot (Allium ascalonicum L.) is one of the important commodities in Indonesia. The main obstacle that is often faced is moler disease caused by Fusarium sp. Bacillus sp. bacteria have the potential to control Fusarium sp. The purpose of study was to determine the ability of Bacillus sp. in controlling moler disease and its effect on the growth and production of onion plants. The study used a factorial completely randomized design with three replications and nine treatments, so there were 27 experimental units. The observation variables included incubation period, disease intensity, plant height, number of leaves, and tuber wet weight. The research data were analyzed using the ANOVA analysis of variance procedure to determine whether there was an effect of each treatment. If it is known that there is a significantly different effect from the treatment, it will be continued with the DMRT test at the 5 % level. The results showed that the combination of Bacillus sp. isolate bcz 16 and dosage 35 ml/polybag was the longest delaying the incubation period of 15 day and could suppress moler disease by 50 %. The treatment of Bacillus sp. isolate bcz 16 and dosage 35 ml also gave the highest results in plant length, number of leaves, and wet weight of shallot bulbs